The use of flow diverting stents to treat para-ophthalmic aneurysms - Bhogal, Pervinder; Bäzner, Hansjörg (Frontiers in neurology, 2017)
Background and Purpose Few publications have dealt exclusively with the use of flow diverter stents for the treatment of para-ophthalmic aneurysms. We sought to determine the efficacy of flow diverting stents to treat aneurysms in this specific location. Methods We retrospectively reviewed our database of prospectively collected information for all patients treated with flow diversion for an unruptured saccular para-ophthalmic aneurysm between September 2009 and January 2016. The aneurysm fundus size, neck size, number and type of flow diverting stent (FDS), complications and follow-up data was recorded. Results We identified 74 patients that matched our inclusion criteria. Of these patients 18 patients were male (24.3%). The average fundus size was 4.8 mm, 11 aneurysms had previous coil occlusions and 63 were treated solely with flow diversion. At an initial angiographic follow-up (mean avg. 3.2 months) 71.8% of the aneurysms were occluded and at the last follow-up (mean avg. 31.8 months) 88.9% of aneurysms were occluded. One patient suffered permanent morbidity (1.36%) secondary to interruption of the anti-platelet medication and another died (1.36%) secondary to in-stent thrombosis that was also due to an interruption in the anti-platelet medication. Conclusion Treatment of saccular para-ophthalmic aneurysms with FDS is feasible and carries a high degree of technical success with low complication rates and excellent rates of aneurysm exclusion.
Gesehen am 05.11.2018